Benefits of glioma resection in the corpus callosum - Marie-Therese Forster (Nature Portfolio, 2020)
Abstract Due to anticipated postoperative neuropsychological sequelae, patients with gliomas infiltrating the corpus callosum rarely undergo tumor resection and mostly present in a poor neurological state. We aimed at investigating the benefit of glioma resection in the corpus callosum, hypothesizing neuropsychological deficits were mainly caused by tumor presence. Between 01/2017 and 1/2020, 21 patients who underwent glioma resection in the corpus callosum were prospectively enrolled into this study. Neuropsychological function was assessed preoperatively, before discharge and after 6 months. Gross total tumor resection was possible in 15 patients, and in 6 patients subtotal tumor resection with a tumor reduction of 97.7% could be achieved. During a median observation time of 12.6 months 9 patients died from glioblastoma after a median of 17 months. Preoperatively, all cognitive domains were affected in up to two thirds of patients, who presented a median KPS of 100% (range 60–100%). After surgery, the proportion of impaired patients increased in all neurocognitive domains. Most interestingly, after 6 months, significantly fewer patients showed impairments in attention, executive functioning, memory and depression, which are domains considered crucial for everyday functionality. Thus, the results of our study strongly support our hypothesis that in patients with gliomas infiltrating the corpus callosum the benefit of tumor resection might outweigh morbidity.